Depuración microbiológica artesanal de la piangua, Anadara tuberculosa (Mollusca: Arcidae) - Wong, Eric (Universidad de Costa Rica, 1997)
In Costa Rica the mollusk Anadara tuberculosa represents a risk for human health due to the contamination of the growing waters and the fact that it is consumed raw. The families depending on the income obtained through cornmercialization of these animals have a low education and economic status. Therefore, it is of great importance to develop and evaluale simple melhods of depuration that could be easily used by these families to make these mollusks safe for consumption. Bottles containing 1 l of saline solution (25g11) were prepared in duplicates to test Ihe bactericidal effect of acetic acid. The solution in each bottle was adjusted to ph 4.5, 5.0 or 5.5 or held at ph of 7.0 or 8.0 for the controls. The solution in each bottle was Ihen inoculated with approximately 1 X 104 cfu/mI of coliforms. Counts of coliforms were determined for each bottle O, 1, 2, 4 and 8 hours after inoculation. For the depuration studies, specimens with diameters ranging fron 4.0 to 4.5 cm were collected form a harvester at Ihe estuary of Puntarenas, Gulf oí Nicoya. Fifty specimens each were depurated in separate tanks containing 25 1 of oxigenated saline solution adjusted with acetic acid to an initial ph of 4.5 (treatment) or non adjusted ph oí 8.0 (control). Counts of Enterobacteriaceae were determined, in duplicates, every 12 hr for 48 hr. An additional fifty animals were depurated using the defined method and tested to determine if they met international standards of microbiological quality for aerobic plate count, Enterobacteriaceae count, Escherichia coli count and presence of Salmonella. A sensory evaluation using a triangle test was performed to compare a typical dish prepared with depurated or non-depurated animals. A significant coliform reduction was determined in a saline solution (25 gil) at a pH range of 4.5 to 5.5 . This reduction, during 8 hr, was higher in Ihe acid treatments compared to Ihe controls. During depuration, the elimination of Enterobacteriaceae bacteria was faster when acetic acid was used (ínitial ph=4.5) Ihan when it was no!. This elimination was more important the first 24 hr, time defined as adequate for the application of Ihe method. The method has the advantage of transforming the bivalve in a product that is safe for human consumption, since it guaranties Ihat the international standards of microbiological quality, for rawand depurated mullusks, are reached. On the other hand, the sensory qualitites oí a typical dish prepared with depurated animals are not affected by the method, which can by easily implemented and applied by Ihe people that work in the extraction of this mollusk ..